Influence of genetic and non-genetic factors on growth performance in Black Bengal goats under field condition in West Bengal - JASMINE, A JEMIMA; SARKAR, UTTAM; ROY, MANORANJAN; DATTA, SANJOY (The Indian Journal of Animal Sciences, 2022)
Data on 10148 Black Bengal kids recorded from 2008 to 2019 and maintained at farmer’s fields at different agroclimatic clusters of West Bengal under the project “AICRP on Goat Improvement, Black Bengal Field Unit- Kolkata” were used to study the effect of non-genetic factors on body weight from birth to 12 months of age. The data were analysed using least squares analysis technique. The average birth weights of Black Bengal goats obtained under four different agro-climatic clusters revealed that there was a significant variation in body weight (kg) of all ages. The effect of year of kidding, influence of season and parity of the dam on body weight of Black Bengal kids at different ages were significant. But a non-significant result was found at the body weight in all the seasons as well as in all the parities at 9 and 12 months of age. Sex of the kid and type of birth had significant effect on body weights from birth to 12 months of age. Significantly higher body weight at birth was recorded in single born kid, followed by twin and triplets. The study concluded that it is possible to improve non-genetic elements in the field, particularly by providing excellent housing, reducing stress, having access to grazing pasture, and doing routine deworming and vaccinations. The findings supported the need for environmental changes that can aid in the development of management strategies and decision making regarding the selection.